Effects of combined exercise program on happiness and life satisfaction on physically active older adults - Romina Herodek; Mladen Živković; Aleksandra Ilić; Katarina Herodek; Aleksandra Catić Đorđević (Exercise and Quality of Life)
Well-being is the assessment of individual experiences with pleasant feelings like happiness and life satisfaction. Combined training is recommended for older adults to decrease age-related psychological changes and functional limitations. This systematic review aimed to assess the effects of a combined exercise program on happiness and life satisfaction in physically active older adults. The electronic databases of Google Scholar, Web of Science, and PubMed were searched between 2000 and 2023 for available literature. The searched keywords were: older adults, training, exercises, happiness, and life satisfaction. After completing the investigation, 931 publications were found. Inclusion criteria comprised physically active participants aged 60 years and above, along with studies composed in English. Studies in which participants had obesity, diabetes, and other non-communicable diseases were excluded from investigation. The qualitative analysis involved eight studies. These studies ranged in publication date from 2008 to 2022. The participants in the studies were men and women aged from 60 to 79 years. The sample size was 1849 and ranged from 35 to 656 participants. Physical activity was a combination of aerobic training, strength training, stretching exercises, and balance exercises. The most used questionnaire was the Satisfaction with Life Scale (SWLS). The findings indicate that older adults of both genders who underwent combined training programs had higher levels of happiness and life satisfaction. Research has shown that leading an active lifestyle enhances older persons' happiness and satisfaction with life. These results support the importance of maintaining an active lifestyle to improve the mental and emotional well-being of older adults.